STUDI PERBANDINGAN KONSEPSI ORGANISASI ISLAM IIIT, ISTAC, DAN ICMI DALAM PEMBANGUNAN PENDIDIKAN - Dede Rubai Misbahul Alam; Reliska Winka Issafila; Novia Putri Khairunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to conduct a comparative analysis of the educational concepts developed by the International Institute of Islamic Thought (IIIT), the International Institute of Islamic Thought and Civilization (ISTAC), and the Indonesian Muslim Intellectuals Association (ICMI). The focus of the study includes the differences and similarities in educational ideology, schools of thought, and the roles and influences of the three organizations in the development of Islamic education, particularly in Indonesia. This study uses a qualitative descriptive method with a literature review approach through the analysis of key books, international journal articles, and institutional documents. The results of the study show that IIIT emphasizes the Islamization of knowledge as an epistemological project, ISTAC focuses on the formation of Islamic manners and worldview in education, while ICMI is oriented towards the integration of Islamic scholarship with national development. All three have made significant contributions to building an integrative and sustainable Islamic education paradigm.